2009
DOI: 10.4314/sajas.v39i2.44390
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of growth curve parameters in Konya Merino sheep (Short communication)

Abstract: The objective of this study was to determine the fitness of Quadratic, Cubic, Gompertz and Logistic functions to the growth curves of Konya Merino lambs obtained by using monthly records of live weight from birth to 480 days of age. The models were evaluated according to determination coefficient (R 2 ), mean square prediction errors (MSPE) and Durbin Watson (DW) statistics. The R 2 values of the models ranged from 0.96 to 0.99 for females and from 0.96 to 0.99 for males. The Cubic model gave the best R 2 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In both sexes, the highest estimates for the B parameter were found for the Logistic model. Similar findings were reported elsewhere (Akbas et al 1999;Bilgin et al 2004a;Keskin et al 2009). The k parameter still indicates the maturing rate, but the parameter from both types of functions is not precisely the same trait among the models.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In both sexes, the highest estimates for the B parameter were found for the Logistic model. Similar findings were reported elsewhere (Akbas et al 1999;Bilgin et al 2004a;Keskin et al 2009). The k parameter still indicates the maturing rate, but the parameter from both types of functions is not precisely the same trait among the models.…”
Section: Resultssupporting
confidence: 92%
“…Parameter estimates, their standard errors (SE), coefficient of determination (R 2 ) and residual squared error (RSE) for nonlinear curves describing growth of body weight (kg) by age (months) in male and female of Hemşin male and female sheep. Similarly, Bathaei and Leroy (1998) Karakus et al (2008), Eyduran et al (2008), Keskin et al (2009), andMalhado et al (2009).…”
Section: Resultsmentioning
confidence: 94%
“…Growth curves models can describe and summarize quantitative changes that birds experiment through their lives, they are useful to select Creole birds according to the producer request and to program feeding phases, focusing a large amount of nutrients on the fast growth phases, to know the optimal age to slaughter, effects of gene selection on curve components, and weight gain on a certain age [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The figure was done based on the estimated parameters presented in (19), when evaluating the same models in sheep (Dorper×Morada Nova, Dorper × Longtail and Dorper × Santa Inés), found that the Gompertz model was the one that best described growth. Keskin et al (20) found that the Quadratic and Gompertz models were the ones that best described the growth of the sheep when evaluating the Quadratic, Cubic, Gompertz and Logistic models in sheep of the Konya Merino breed.…”
Section: Growth Curvesmentioning
confidence: 99%